The verbal periphrasis of infinitive constructions in the Spanish of children in La Mar district (Ayacucho Region) - Esquivel Villafana, Jorge (2017)
The current study focuses on the description of verbal periphrasis of infinitive constructions in the Spanish of children in La Mar district (Ayacucho Region), an Andean area of Spanish and Quechua languages in contact, located in the South of Peru. Given the nature of the research, this will be of syntactic and semantic type.